Impact of landscape patterns on solute dynamics during hydrological events: A multiscale study in the upper Han River basin - Xi Jiang; Jiasheng Wang; Xiaoguang Liu; Shouhang Chen; Lingqi Yi (Ecological Indicators)
A multi-scale analysis was conducted to examine how landscape patterns influence solute dynamics during hydrological events in the upper Han River basin. High-frequency water quality data from six sub-watersheds in 2023 were utilized to evaluate hydrological and hydrochemical processes under contrasting flow conditions. Concentration–discharge hysteresis metrics (FI and HI) were applied to characterize the flushing and lag effects of dissolved oxygen (DO), turbidity (TU), total phosphorus (TP), and total nitrogen (TN). Redundancy analysis (RDA) was employed to quantify the relationships between landscape indicators and solute export at both the riparian buffer and sub-basin scales. It was found that TU, TP, and TN exhibited pronounced flushing behavior (FI > 0) during hydrological events, with intensified counterclockwise hysteresis in the high-water season (HW). In particular, FI values exceeded 0.8 for TU, TP, and TN during the HW. During the usual-water season (UW), FI values for the same solutes averaged around 0.4 across several sub-basins. Greater explanatory power for solute flushing was provided by riparian buffer delineation, whereas sub-basin delineation offered better insight into the counterclockwise hysteresis patterns. Cultivated land ratio and landscape shape index (LSI) were identified as key factors influencing the flushing and lag characteristics of solutes, while forest coverage played an important role in moderating solute delivery during HW periods. These findings reveal the coupling mechanism between flood-induced solute transport and landscape configuration in mountainous basins. It is suggested that the conservation of forest areas, rational distribution of agricultural land, and the design of riparian buffer zones should be considered at multiple spatial scales to mitigate water quality risks during high water level periods. The findings support the strategic deployment of riparian buffers to reduce sediment and nutrient loading during high water level events, and the incorporation of forest preservation and agricultural land use planning at the sub-basin level to mitigate long-term water quality risks.